Vaccine hesitancy and economic hardship: A latent class analysis of racial and ethnic minority communities at high risk of COVID-19 infection in Southern California - Britt Skaathun; Christian I. Rodríguez-Rosales; Grethel Gahbler-Lopez; Scott R. Furtwengler; Linda Salgin; Fatima A. Muñoz; Davey M. Smith; Jamila K. Stockman; Sophie E. O’Bryan; Daniel Ramirez; Cynthia James-Price; Argentina E. Servin (Human Vaccines & Immunotherapeutics)
We examined the association between economic hardship and vaccine hesitancy among communities at high risk of COVID-19 infection. We used latent class analysis to calculate the predicted probability of belonging in a high or low vaccine hesitancy group using nine vaccine belief and behavior survey items using data from clinical trial NCT05022472. An economic hardship index was constructed to assess whether experiencing one or more economic hardships during the COVID-19 pandemic was associated with high vaccine hesitancy using a multivariable logistic regression model. Overall, 39% of participants remained highly vaccine hesitant despite vaccine uptake exceeding 97%, highlighting the important distinction between uptake and hesitancy. Having experienced at least one economic hardship significantly increased the adjusted odds of high vaccine hesitancy, compared to not experiencing any economic hardships. Employment, infection history, education, and vaccine series completion factors were also salient factors associated with high vaccine hesitancy. Future research should explore the impact of targeted financial and policy interventions in fostering vaccine confidence.